2014
DOI: 10.1089/sur.2013.005
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Contraceptive Device-Related Actinomycosis Infection Presenting as Ovarian Cancer with Carcinomatosis

Abstract: Surgeons and clinicians should be aware of this infectious disease because of its atypical symptoms and potential to mimic soft tissue tumors or malignant neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Thus, the endometrium post-pregnancy is more vulnerable, accounting for approximately 90% of all IUAs, most often following natural childbirth, cesarean section, or abortion. In this study, we examined 121 cases of secondary infertility (86.4%), and only 19 cases of primary infertility (13.6%), suggesting that secondary infertility causes IUAs more often, in agreement with the findings of the previous study mentioned (9).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, the endometrium post-pregnancy is more vulnerable, accounting for approximately 90% of all IUAs, most often following natural childbirth, cesarean section, or abortion. In this study, we examined 121 cases of secondary infertility (86.4%), and only 19 cases of primary infertility (13.6%), suggesting that secondary infertility causes IUAs more often, in agreement with the findings of the previous study mentioned (9).…”
Section: Discussionsupporting
confidence: 90%
“…Intrauterine infections are also an important cause of IUAs (8). IUAs can also occur in patients with non-tuberculous endometritis and lacking a history of intrauterine surgery; in fact, Lim et al demonstrated that postpartum or post-surgical low estrogen levels affected the repair of the endometrium, leading to IUAs (9). Thus, the endometrium post-pregnancy is more vulnerable, accounting for approximately 90% of all IUAs, most often following natural childbirth, cesarean section, or abortion.…”
Section: Discussionmentioning
confidence: 99%
“…The second case corresponds to a tubo-ovarian localization, more frequently reported in the literature, especially in a patient Case study with prolonged IUD use associated with a long history of abdominal pain, anorexia, weight loss, and pelvic tumor mass. 9 In most reports, the diagnosis of pelvic actinomycosis occurs in women younger than 50 years old, 10 and only 10% of the cases are diagnosed before surgery. First, clinical manifestations are nonspecific, consisting of fever, leukocytosis, weight loss, fatigue, and abdominal pain.…”
Section: Dr Saez Perrottamentioning
confidence: 99%
“…The nonspecific findings complicate the differential diagnosis of abdominopelvic actinomycosis from other chronic diseases such as chronic granulomatous infection, inflammatory bowel disease, and pelvic inflammatory diseases. Furthermore, it often presents as a mass either clinically or radiologically, which is not easily distinguishable from malignancies [ 12 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%